The Effect Of Tax Incentives And Tax Understanding On MSME Taxpayer Compliance (Empirical Study Tax Office Pratama Subang) - Vivi Damayanti (LPPM Universitas Sebelas April, 2023)
The core problem of this research is the low compliance of MSME taxpayers at KPP Pratama Subang. This study used a quantitative method with a survey approach and the population was taken from the number of MSME taxpayers registered at KPP Pratama Subang, which amounted to 26,466 so that the sample obtained from the calculation of the slovin formula was 100 respondents. Data collection was carried out by distributing questionnaires using simple random sampling method. The data analysis technique uses Statistical Package For Social Science (SPSS) 25. The test results for the coefficient of determination between Tax Incentives and Tax Understanding on MSME Taxpayer Compliance is 80.5%, this shows that the other 19.5% is influenced by other factors that are not included in the variables of this study. Based on the results of the study, it shows that tax incentives have a significant effect on MSME taxpayer compliance, tax understanding has a significant effect on MSME taxpayer compliance, tax incentives and tax understanding simultaneously have a positive and significant effect on MSME taxpayer compliance.